The Porn Myth Exposing the Reality Behind the Fantasy of Pornography. - Fradd, Matthew (Ignatius Press, 2017)
"The Porn Myth is a non-religious response to the commonly held belief that pornography is a harmless or even beneficial pastime. Author Matt Fradd draws on the experience of porn performers and users, and the expertise of neurologists, sociologists, and psychologists to demonstrate that pornography is destructive to individuals, relationships, and society. He provides insightful arguments, supported by the latest scientific research, to discredit the fanciful claims used to defend and promote pornography. This book explains the neurological reasons porn is addictive, helps individuals learn how to be free of porn, and offers real help to the parents and the spouses of porn users. Because recent research on pornography's harmful effects on the brain validates the experiences of countless porn users, there is a growing wave of passionate individuals trying to change the pro-porn cultural norm by inspiring others to pursue real love and to avoid its hollow counterfeit" --Inside cover.